2015
DOI: 10.1007/s00262-015-1729-x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring regulatory T cells in clinical samples: consensus on an essential marker set and gating strategy for regulatory T cell analysis by flow cytometry

Abstract: Regulatory T cell (Treg)-mediated immunosuppression is considered a major obstacle for successful cancer immunotherapy. The association between clinical outcome and Tregs is being studied extensively in clinical trials, but unfortunately, no consensus has been reached about (a) the markers and (b) the gating strategy required to define human Tregs in this context, making it difficult to draw final conclusions. Therefore, we have organized an international workshop on the detection and functional testing of Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
145
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 54 publications
(67 reference statements)
6
145
0
2
Order By: Relevance
“…To determine whether Tregs from patients with PMF maintained the same antiproliferative activity on effector T cells, we cocultured CD4 21 Normal subjects had a median blood Treg frequency of 1.99% (range, 0.48-6.51). In contrast, subjects with PMF had a median Treg frequency of 0.80% (range, 0-10.2; Mann-Whitney U test, P , .001).…”
mentioning
confidence: 99%
“…To determine whether Tregs from patients with PMF maintained the same antiproliferative activity on effector T cells, we cocultured CD4 21 Normal subjects had a median blood Treg frequency of 1.99% (range, 0.48-6.51). In contrast, subjects with PMF had a median Treg frequency of 0.80% (range, 0-10.2; Mann-Whitney U test, P , .001).…”
mentioning
confidence: 99%
“…Foxp3 expression within the isolated Tregs was determined after subsequent staining with PE-CF594-labeled Foxp3 monoclonal antibody (clone 259D/C7, BD) using the BD Pharmingen Transcription Factor Buffer set as described before. 45 Gating strategies for FACS sorting, purity check and characteristics of the isolated populations are given in suppl. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…24 and Santegoets, et al .. 25 Cryopreserved PBMCs were thawed and washed twice in cold PBS. Dead cells were stained using LIVE/DEAD Fixable Aqua Dead Cell Stain (Invitrogen life technologies, Cat# L34957).…”
Section: Methodsmentioning
confidence: 99%
“…Santegoets et al . 25 showed that the frequency of aTregs and proliferating Ki67 + FoxP3 + CD25 + CD127 low Tregs prior to treatment were associated with worse survival in recurrent ovarium carcinoma patients undergoing chemo-immunotherapeutic treatment, whilst frequencies of classically defined Tregs prior to treatment were not associated with survival. In mesothelioma, Tregs contribute to an impaired T cell function 26,27 and are associated with tumor progression and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%